Arylphosphonate-Tethered Porphyrins: Fluorescence Silencing Speaks a Metal Language in Living Enterocytes** - Keil, Claudia; Klein, Julia; Schmitt, Franz-Josef; Zorlu, Yunus; Haase, Hajo; Yuecesan, Guendog (Wiley-V C H Verlag Gmbh, 2021)
We report the application of a highly versatile and engineerable novel sensor platform to monitor biologically significant and toxic metal ions in live human Caco-2 enterocytes. The extended conjugation between the fluorescent porphyrin core and metal ions through aromatic phenylphosphonic acid tethers generates a unique turn off and turn on fluorescence and, in addition, shifts in absorption and emission spectra for zinc, cobalt, cadmium and mercury. The reported fluorescent probes p-H(8)TPPA and m-H(8)TPPA can monitor a wide range of metal ion concentrations via fluorescence titration and also via fluorescence decay curves. Cu- and Zn-induced turn off fluorescence can be differentially reversed by the addition of common chelators. Both p-H(8)TPPA and m-H(8)TPPA readily pass the mammalian cellular membrane due to their amphipathic character as confirmed by confocal microscopic imaging of living enterocytes.
Keywords: Caco-2; fluorescence sensors; homeostasis; metals; time-resolved fluorescence